Mental health interventions affecting university faculty: a systematic review and meta-analysis - Dalal Hammoudi Halat; Waqas Sami; Abderrezzaq Soltani; Ahmed Malki (BMC, 2024)
Abstract Background While there is growing evidence highlighting the prevalence of mental health concerns among university faculty, few studies have examined mental health interventions in this population. The objective of this systematic review and meta-analysis was to collect and critically appraise the available evidence about the effectiveness of interventions designed to improve the mental health of faculty. Methods A systematic search was conducted by searching PubMed, EMBASE, Scopus, Web of Science, and CINAHL to identify relevant studies published in English language from January 1st, 2000 until October 1st, 2023. The search focused on studies done on academic faculty to describe interventions or support programs aimed at improving mental health outcomes, with comparison of mental health data before and after the intervention and an improvement in mental health as study outcome. A random effect meta-analysis method was used to estimate the effectiveness of interventions on faculty mental health. Results Ten publications with 891 participants from 2,217 retrieved records were included. The random effect model showed substantial heterogeneity (I2 = 84.8%, 95% CI: 73.8 − 91.2%, p < 0.001). The pooled SMD was − 1.41 (95% CI: -2.81-0.004) showing a large effect, and it significantly favors the use of intervention for reducing mental health issues among faculty members. The effect size estimates for all included studies ranged from small to large, showing the positive effect of intervention on faculty mental health. Multimodal inference analysis showed that, of the many studied factors for faculty mental health, the region was the most important predictor of intervention effectiveness. However, when the significance of quantitative moderators was tested using meta-regression, age (p = 0.9491) and duration of intervention (p = 0.1284) were not statistically significant. Conclusion Interventions aimed at enhancing the mental health of university faculty were overall significant; however, individual studies showed heterogeneous results. Making efforts to enhance the mental health of faculty is crucial and has been proven effective; nevertheless, the existing evidence necessitates further research in this area. For interventions to be effective, it is imperative to tailor them to the specific environment and to the unique characteristics of faculty members. PROSPERO registration number CRD42023490388